Higher remnant cholesterol increases the risk of coronary heart disease and diabetes in postmenopausal women - Zhang, Yan; Song, Kexin; Bi, Shuli; Li, Mingyang; Yao, Zhuhua (Frontiers in Endocrinology, 2024)
Background: Postmenopausal women represent the demographic increasingly susceptible to cardiovascular and metabolic diseases. Elevated levels of remnant cholesterol (RC) have been implicated in atherosclerosis and insulin resistance.Methods: This study aimed to investigate the relationship between RC and the prevalence of coronary heart disease (CHD), diabetes, and CHD combined with diabetes in a nationally representative sample of US postmenopausal women using data from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. Multivariate logistic regression models were employed to evaluate the association between RC and the outcomes of interest. Nonlinear relationships were examined using restricted cubic splines (RCS), and subgroup analyses and interaction tests were conducted.Results: A total of 1611 participants were included in the final analysis. Higher RC levels were significantly associated with increased risks of CHD [OR=1.67, 95%CI (1.02, 2.74)], diabetes [OR=1.77, 95%CI (1.22, 2.58)], and CHD combined with diabetes [OR=2. 28, 95%CI (1.17, 4.42)] (all P<0.05). Compared to the lowest RC quartile (Q1), the highest quartile (Q4) demonstrated elevated incidences of CHD [OR=1.76, 95%CI (1.04, 2.98)], diabetes [OR=1.81, 95%CI (1.30, 2.53)], and CHD combined with diabetes [OR=3. 08, 95%CI (1.29, 7.37)] (all P<0.05). RCS curves indicated a nearly linear relationship between RC and the risks of CHD, diabetes, and CHD combined with diabetes.Our study reveals a significant positive correlation between RC levels and the prevalence of CHD, diabetes, and CHD combined with diabetes among postmenopausal women. Understanding these associations could potentially inform targeted prevention and management strategies tailored to this vulnerable population.